Hak Atas Privasi dalam Pengelolaan Digital Legacy Pascakematian sebagai Wujud Perlindungan Hak Asasi - Kadek Ayu Widya Arisanthi (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of technology communication and information has produce the phenomenon of digital legacy, which is a person's digital footprint that remains stored and persists after they pass away.This digital legacy not only reflects a person's identity and personal life but also stores sensitive and private data.In the perspective of human rights, the right to privacy is a base right that must be protected, including personal data post-mortem. However, the legal system in Indonesia has not explicitly regulated the protection of digital legacy, resulting in a legal vacuum that potentially violates the right to privacy.This research uses a normative method with a legislative approach and a case approach.The study results show that the absence of national legal norms specifically regulating digital legacy causes society to depend on the internal policies of foreign digital platforms, which do not guarantee justice and human rights protection. National regulations are needed that specifically govern the protection of personal data post-mortem as a form of respect for human privacy and dignity, as well as a tangible manifestation of the state's responsibility to guarantee the human rights of its citizens in the digital era.